2017
DOI: 10.1038/s41598-017-09815-9
|View full text |Cite
|
Sign up to set email alerts
|

A Biomimetic Microfluidic Tumor Microenvironment Platform Mimicking the EPR Effect for Rapid Screening of Drug Delivery Systems

Abstract: Real-time monitoring of tumor drug delivery in vivo is a daunting challenge due to the heterogeneity and complexity of the tumor microenvironment. In this study, we developed a biomimetic microfluidic tumor microenvironment (bMTM) comprising co-culture of tumor and endothelial cells in a 3D environment. The platform consists of a vascular compartment featuring a network of vessels cultured with endothelial cells forming a complete lumen under shear flow in communication with 3D solid tumors cultured in a tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 65 publications
9
96
0
Order By: Relevance
“…After 24 h, a complete and confluent layer of HUVECs was observed by both bright field and confocal microscopy (Figure B,C). It has been demonstrated that endothelial cells cultured under such flow conditions have similar morphology and function to that observed in vivo . To further verify the complete formation of a 3D lumen of HUVECs on the top, bottom, and side of the microchannels, an Eclipse TiE Microscope with a Nikon A1R Confocal was utilized to acquire a 3D Z‐stack of the synthetic vessels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After 24 h, a complete and confluent layer of HUVECs was observed by both bright field and confocal microscopy (Figure B,C). It has been demonstrated that endothelial cells cultured under such flow conditions have similar morphology and function to that observed in vivo . To further verify the complete formation of a 3D lumen of HUVECs on the top, bottom, and side of the microchannels, an Eclipse TiE Microscope with a Nikon A1R Confocal was utilized to acquire a 3D Z‐stack of the synthetic vessels.…”
Section: Resultsmentioning
confidence: 99%
“…After the microfluidic chip was successfully coated with HUVECs, nanoparticle suspension in EGM (at 37 °C) was introduced into the SMN at a flow rate of 1.0 µL min −1 . This flow rate was selected to create a physiological shear rate range (from ≈30 to ≈240 s −1 ) found in vivo . After 4 h, chilled 4‐(2‐hydroxyethyl)‐1‐piperazineethanesulfonic acid (HEPES) buffered saline solution (HBSS) was injected to remove non‐associated nanoparticles from the microchannels before HUVECs were collected for analysis by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…c) A biomimetic platform co‐culturing human breast tumor associated endothelial cells (HBTAEC) and MDA‐MB‐231 cancer cells in vascular and tumor compartments to analyze the permeability of endothelial cells. Reproduced with permission . Copyright 2017, Springer Nature Publishing AG.…”
Section: Microfluidic Platforms For Engineered Tumor Microenvironmentmentioning
confidence: 99%
“…tests under conditions that more closely resemble those found in vivo. 5 With careful design, these systems can also mimic the in vivo sheer stress of blood and cells in contact with blood flow, which allows them to function normally. [6][7][8] In the same way, care must be taken to avoid exposing cells to unwanted sheer stress as both cell morphology and physiology can be affected.…”
Section: Scanning Electron Microscope (Sem) Images Of the Monolith Crmentioning
confidence: 99%